Exploring the relationship between nurses' communication satisfaction and patient safety culture - Linda Wieke Noviyanti; Ahsan Ahsan; Tita Sefti Sudartya (SAGE Publishing, 2021)
Background: Patient safety culture is associated with the values, attitudes, competencies and behaviors that support the safe conduct of individual or group activities in hospitals and other health organizations. Safety culture is influenced by various factors, one of which is communication, which plays a significant role in health services. Therefore, this study aims to analyze the relationship between nurse communication satisfaction and the quality of patient safety culture in hospitals.  Design and Methods: This is a cross-sectional design with the proportional random sampling method used to data from 51 nurses, which was analyzed using the Spearman rank test. The majority of the nurses were female, between 20 - 30 years old, with 1-5 years working experience. Results: The results showed a significant relationship between nurse communication satisfaction and the quality of patient safety culture. Furthermore, the higher the nurses' level of communication satisfaction, the better the applied quality of patient safety culture (r = 0.338). ConclusionS: Nurse communication satisfaction affects the provision of effective health care, with the ability to create good cooperative relationships and foster trust between professions in order to improve the quality of service delivery and patient safety.